The effect of teaching using Kolb’s model in Skills development of students of the Art Education Theatrical Directing (Al-Academy, 2024)
(Learning about the invention of teaching using the Kolb model in developing the skills of students of the Department of Art Education in the subject of theater directing). To achieve the research objectives, the researcher formulated a null hypothesis to discuss the results. The researcher adopted the experimental method, specifically the two-sample design (experimental and control). The research sample was (26) students In the Department of Art Education, College of Fine Arts /Diyala. The researcher conducted parity between the two research groups in the number of the variables, then the two groups were taught for a period of (8) weeks, and to measure the achievement of the members of the two research samples, the researcher built a tool for his research, which is the observation form, which consisted of (10) items on a five-point scale, and the researcher extracted validity and reliability for it. As for statistical methods, several methods were applied to address Data through the statistical package (Spss)The results of the research resulted in the effect of teaching using the Kolb model in developing the skills of students of the Art Education Department in the theatrical directing subject In light of the results reached by the researcher, the research concluded with a set of conclusions, recommendations, and proposals